2010
DOI: 10.1063/1.3430570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vacuum ultraviolet and ultraviolet irradiation on ultrathin hafnium-oxide dielectric layers on (100)Si as measured with electron-spin resonance

Abstract: The effects of vacuum ultraviolet (VUV) (7.2 eV) and UV (4.9 eV) irradiation on hafnium-oxide dielectric layers were studied with electron-spin resonance to detect defect states. Silicon dangling-bond defects (Pb centers) and positively charged oxygen vacancies (E′ centers) were detected with g-factor fitting. VUV irradiation increases the level of Pb states, while UV decreases the level of Pb states but increases the level of E′ states significantly. Rapid thermal annealing appears to mitigate these effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Thus, exposure to UVA processing resulted in a three order of magnitude reduction of the films leakage characteristics. Similar reduction in leakage characteristics have been observed for Ta 2 O 5 films UV-annealed (172 nm eximer lamp) at 400 C/ 60 min, 37 Ta 2 O 5 films grown by photo-pulsed laser vapor deposition PLD, 38 for UVA HfO 2 films (mercury lamp), 46 and for BST films grown by UV-PLD. 47 Our results demonstrated that the reduction in leakage current density (Fig.…”
Section: Resultssupporting
confidence: 74%
“…Thus, exposure to UVA processing resulted in a three order of magnitude reduction of the films leakage characteristics. Similar reduction in leakage characteristics have been observed for Ta 2 O 5 films UV-annealed (172 nm eximer lamp) at 400 C/ 60 min, 37 Ta 2 O 5 films grown by photo-pulsed laser vapor deposition PLD, 38 for UVA HfO 2 films (mercury lamp), 46 and for BST films grown by UV-PLD. 47 Our results demonstrated that the reduction in leakage current density (Fig.…”
Section: Resultssupporting
confidence: 74%
“…Plasma-induced defect creation has been studied in great detail for the plasma processing of SiO 2 -based gate stacks 299,300,[346][347][348][349] and the influence of VUV exposure has also recently been studied for the high-k oxide HfO 2 . 299,300,344,[350][351][352] However, this damage mechanism has not really been highlighted for plasma-assisted ALD processes, for example, during the synthesis of metal oxides by plasma-assisted ALD itself or when depositing other materials (such as electrode materials) on top of high-k oxides by plasma-assisted ALD. Note that, apart from the fact that the metal oxide film might itself be affected, the interfacial SiO x layer, which is typically present (either unintentionally or prepared on purpose) between the metal oxide and the Si substrate, can also be affected.…”
Section: Challenges Of Plasma-assisted Aldmentioning
confidence: 99%
“…7,8 Previous work using ESR shows that HfO 2 has numerous defect states. 9 The most common are Pb-type (Pb0 and Pb1), E 0 , etc. 9 The Pb-type states are silicon dangling bonds.…”
mentioning
confidence: 99%